Structural robustness - FE methodology for analysing alternate load paths in buildings - Kjellman,Axel (TVSM-5000, 2017)
Robust structures are necessary in order to avoid a progressive collapse if a local failure occurs, for instance, failure of a column. Robustness is achieved in structures by designing them for so-called accidental actions, such as an explosion or a vehicle impact. These actions are often unexpected, sudden and local as they act on a limited part of the structure. It should be emphasised that progressive collapse design is about avoiding a collapse due to a local failure and not due to an abnormal load on the entire structure. There are two main strategies often used in progressive collapse design. One strategy is to use a general method that aims to provide enough robustness and continuity in the structure. Another strategy for the designer is to show, by notional removal of elements, for instance, a column, that the structure can enable alternate load paths and therefore remains stable. Even though no assurance is made that the structure is robust using the general method, it is the most commonly used method, partially due to an absence of guidance in regulations of how the notional removal strategy should be performed. The advantage of the notional removal strategy is that it provides an understanding of the actual performance of the structure. In the USA, the Department of Defence has developed guidance on how numerical analysis using the finite element method should be used to validate the structure’s robustness. In the thesis, progressive collapse analysis of a structure has been performed, inspired by the methods used in the USA, to provide knowledge of how numerical models can be used to validate robustness. The main focus of the thesis has been to examine if linear, non-linear or dynamic effects are needed in the analysis and how detailed the models need to be. By comparing results from 2D and 3D analyses, it is questionable if a 2D model is accurate enough to represent all load carrying mechanisms that are present in the event of a column failure. When only linear effects were included in the analysis, it resulted in conservative results. Progressive collapse design is based on the advantage of large deformations and displacements, which are effects that could not be utilised in a linear analysis. However, with non-linear analyses, these effects are included which lead to an essential capacity increase due to a development of cable action in the beams. Results from the analyses showed that a non-linear static analysis could replace a dynamic analysis by adding an extra load on the structure to account for the dynamic effects. It is beneficial if the dynamic analysis could be avoided due to its high computational cost.
Keywords: accidental action; robustness; finite element method; FE; dynamics; progressive collapse; redundancy; alternate path; notional removal; precast